Real-world fuel-based and tillage area-based emission factors of agricultural machines during different tillage processes - Shen, Xianbao; Yu, Wenhan; Yao, Zhiliang; Kong, Lei; Wu, Bobo; Xuan, Kaijie; Cao, Xinyue; Li, Xin; Zhang, Hanyu; Hao, Xuewei; Zhou, Qi (Frontiers in Environmental Science, 2022)
Emissions of agricultural machines during tillage processes played an important role in severe seasonal pollution events in agricultural areas in China and cannot be ignored. In this study, the CO, NOX, HC and PM2.5 emissions of agricultural machines during real-world tillage processes were tested using a portable emission measurement system (PEMS), and their fuel-based and tillage area-based emission factors were calculated. The CO, NOX, HC and PM2.5 emissions were influenced by emission standards, engine rated power, tillage processes and crops. Only the CO, HC and PM2.5 fuel-based emission factors were reduced from China 0 to China II. For China III agricultural machines, the fuel-based emission factors were higher during plowing and tilling than during harvesting. The tillage area-based CO, NOX, HC and PM2.5 emission factors of corn tillage process were 11.85 ± 8.30, 53.21 ± 48.80, 3.46 ± 3.14 and 1.64 ± 1.33 kg/km2, respectively. The tillage area-based CO, NOX, HC and PM2.5 emission factors of wheat tillage process were 19.69 ± 21.50, 79.98 ± 63.22, 3.90 ± 2.96 and 1.61 ± 2.43 kg/km2, respectively. The tillage area-based emission factors of China III agricultural machines during plowing and tilling were higher than those during harvesting. The fuel consumption per unit tillage area can be used to provide a reference for the interconversion of the two emission factors in future studies. By comparing the fuel-based emission factors in this study with those in the Guidelines and other studies, we observed that the CO, HC and PM2.5 emissions of agricultural machines with corresponding emission standards may be overestimated and the NOX emissions may be underestimated in areas where wheat and corn are mainly grown. Moreover, the pollutant emissions of agricultural machines were regionally different. These results could help elucidate the pollution contribution of agricultural machines in China.